Improving the Levels of Geometric Thinking of Secondary School Students Using Geometry Learning Video based on Van Hiele Theory - Mohd. Salleh Abu; Zaid Zainal Abidin (Institute of Advanced Engineering and Science, 2013)
An educational video called Video Pembelajaran Geometri (Geometry Learning Video = VPG) is developed in this study. The video is aimed to help year 9 students in improving their level of Van Hiele geometrical thinking. VPG is designed as an alternative aids to overcome the limitation of information and communication technology (ICT) usage in Parepare, South Celebes, Indonesia. Based on Van Hiele learning model, all topics in geometry for Indonesian Secondary School (Sekolah Menengah Pertama = SMP) are included in VPG in order to support the students who are going to continue their study further. The effectiveness of VPG was tested on 180 students categorized as 90 students from level 0 (L0), 60 students from level 1 (L1), and 30 students from level 2 (L2). Comparative Analyses on the results of adapted Van Hiele Geometry Test (VHGT) pre and post VPG usage indicated that there is a significant difference between the mean scores. It was also discovered that a significant improvement in geometric thinking level is occurred in the majority of the students.DOI: http://dx.doi.org/10.11591/ijere.v2i1.1935